The Contribution of Social Capital to Waste Management for Street Vendors in Semarang City, Indonesia - Eko Handoyo; Lailasari - Ekaningsih; Islakhul Grace Saadah (Komunitas, 2023)
Garbage is a serious issue faced by all governments in the world. If a government does not handle waste well, then it will become a much bigger problem. The city of Semarang has this problem. This research is conducted to solve (1) what efforts street vendors use to manage their waste and (2) how social capital contributes to waste management. This study is conducted with quantitative and qualitative methods. Quantitative methods are used to answer the first research problem, and qualitative methods are used to answer the second research problem. The results of this research show that (1) street vendors’ efforts to manage their waste only involve disposing of waste and focusing on reducing waste and (2) social capital, which is a social norm that contributes to waste management by street vendors, includes commitment and obedience from street vendors to dispose of their trash and keep their areas clean.